Công nghệ sản xuất da trâu chun mặt tự nhiên làm bọc đệm - Trần, Thị Nhàn (2011)
Tác giả: Trần Thị Nhàn, KS; Nguyễn Hữu Cường, KS; Nguyễn Bạch Yến, KS; Nguyễn Trí Hạnh, PTS; Nguyễn Chí Kiên, KS -- Từ khóa: Công nghệ gia công; Da trâu chun mặt; Da cao cấp; Da bọc đệm